Pandemic, politics, and a fairer society in Southeast Asia : a Malaysian perspective - Shukri, Syaza (Diverse perspectives on creating a fairer society, 2023)
While the world was swept up in the complications and uncertainty of the COVID-19 pandemic, Malaysia's government changed leadership twice without going to ballot. Employing the Malaysian case as a starting point for examining a wider trend in Southeast Asia, Pandemic, Politics, and a Fairer Society in Southeast Asia delves into how politicians and policymakers navigate political uncertainty and the impact of their decisions on creating and maintaining a fairer society. Presenting perspectives from political scientists from across Malaysia and the SEA region, chapters base themselves in the circumstances of political upheaval that Malaysia faced during the pandemic, making a unique and critical contribution to literature on the Southeast Asian experience of COVID-19. Covering trends in Southeast Asia, public perception, elections, and governance, contributors chronicle the rise of regional governments that sought to increase populism and authoritarianism at the height of the pandemic, in addition to monitoring the ongoing fluctuation of public trust and its relation to the political landscapes of the region. With a special focus on creating a fair and just society for a sustainable future, Pandemic, Politics, and a Fairer Society in Southeast Asia offers an in-depth analysis of regional political dynamics from multiple disciplines, including international relations, philosophy, and gender studies.